2018
DOI: 10.1055/s-0038-1639594
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HIV and Antiretroviral Treatment on Auditory Functions

Abstract: Introduction  Numerous studies have evaluated auditory functions in human immunodeficiency virus (HIV) patients; however, these studies had a few major limitations in terms of methodology as they used mainly evoked audiometry although this method is expensive, time consuming and not widely available. Therefore, we conducted a study in naïve HIV subjects with routine audiometry. Objective  To determine the effect of HIV and of the drugs used to treat it on the auditory functions. Methods  A prospective observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…The exposure to the treatment for more than one month, the AG-based regimen, age ≥ 40 years, hypoalbuminemia, and CKD were identified as the main determinants of the hearing loss among the patients with MDR-TB. These data are consistent with those reported in the literature [4] In this study, a positive HIV serology and a BMI < 18.5 kg/m 2 were not associated with the hearing loss in the patients with MDR-TB, although HIV manifests tropism for the auditory nerve and the ototoxicity exacerbated by antiretroviral drugs [40]. Some authors have demonstrated that a BMI of < 18.5 kg/m 2 before the initiation of the treatment and a positive HIV serology are strongly Int.…”
Section: Determinants Of Hearing Losssupporting
confidence: 92%
“…The exposure to the treatment for more than one month, the AG-based regimen, age ≥ 40 years, hypoalbuminemia, and CKD were identified as the main determinants of the hearing loss among the patients with MDR-TB. These data are consistent with those reported in the literature [4] In this study, a positive HIV serology and a BMI < 18.5 kg/m 2 were not associated with the hearing loss in the patients with MDR-TB, although HIV manifests tropism for the auditory nerve and the ototoxicity exacerbated by antiretroviral drugs [40]. Some authors have demonstrated that a BMI of < 18.5 kg/m 2 before the initiation of the treatment and a positive HIV serology are strongly Int.…”
Section: Determinants Of Hearing Losssupporting
confidence: 92%
“…A variety of studies have hypothesized that HIV, while present in the CNS, has its direct effect on the vestibular and cochlear system as well as more central auditory processing pathways (13, 27, 28). As demonstrated by Matas et al and Maro et al MLR latencies and gap detection thresholds were prolonged as a measurement for central auditory processing (2, 13).…”
Section: Discussionmentioning
confidence: 99%
“…This observation did not show a significant difference. 7 In this study, age factor affected hearing loss in HIVinfected patients who received ARVs (p=0.023). Patients in the group 19 to <35 years old had a three times higher risk of developing hearing loss (RP: 3.818).…”
Section: Discussionmentioning
confidence: 64%